A linguist looks at AAC: Language representation systems for augmentative and alternative communication, compared with writing systems and natural language. Issue 1 (2nd January 2016) - Tenny, Carol
Abstract : Writing systems are technological innovations that make it possible to record and reproduce the spoken utterances in a human language. They are the oldest, but not the only, kind of language representation system developed by human technology. The field of Augmentative and Alternative Communication (AAC) has created various technologies to facilitate communication for people who cannot communicate through language in the normal way. Users of AAC devices are persons with a physical or mental disability which compels them to produce speech using a technological device; and these persons depend on the Language Representation System (LRS) associated with their particular device in order to communicate. The purpose of this paper is twofold: first, to introduce the kinds of Language Representation Systems used in AAC devices to the audience of this journal; and second, to compare these LRSs with written language. In making this comparison, I show that they are forced into certain inevitable parallels by the structure of natural language which they must represent. They obey the same constraints, among these the impossibility of a truly semantic language representation system. In this paper, I illustrate the range of these LRSs used in AAC devices by illustrating and comparing three different systems, using a tripartite taxonomy of these systems. The three systems are compared with each other and with writing systems, focusing on how they map to the linguistic units of natural language and the compositional structure of natural language. I focus on a subset of the population employing AAC devices: those persons who are physically impaired but cognitively intact; and whose linguistic ability is comparable to any person who communicates through language in the normal way. Next, I compare one of these systems, with the writing system for Japanese, and show that they have converged on some similar responses to different engineering challenges. Finally, I propose that writing systems should be regarded as a subclass of a larger set of Language Representation Systems, of which both they and these LRSs for AAC technology are members.